Analysis of carbon dioxide emission of gas fuelled cogeneration plant - Nordin, A. (2013)
Gas turbines are widely used for power generation. In cogeneration system, the gas turbine generates electricity and the exhaust heat from the gas turbine is used to generate steam or chilled water. Besides enhancing the efficiency of the system, the process assists in reducing the emission of CO2 to the environment. This study analyzes the amount of CO2 emission by Universiti Teknologi Petronas gas fuelled cogeneration system using energy balance equations. The results indicate that the cogeneration system reduces the CO2 emission to the environment by 60. This finding could encourage the power plant owners to install heat recovery systems to their respective plants. Â© Published under licence by IOP Publishing Ltd.